Improved methods for the cultivation of strictly anaerobic, extremely thermophilic methanogens - Foster, M S (BioTechniques, 1993)
The strictly anaerobic, extremely thermophilic methanogens, Methanobacterium thermoautotrophicum Marburg and M. thermoautotrophicum delta H, have been cultivated in liquid culture and on solid medium in screw-top bottles, which permit continuous monitoring of the growth of the microorganisms. We have been able to routinely grow methanogens in medium containing bicarbonate, TRIS or 4-morpholinepropanesulfonic acid (MOPS) buffers and three different sulfur sources (sulfide, sulfite and thiosulfate) at temperatures up to 70 degrees C and at pressures up to 35 psi while monitoring cell density or colony formation